Stochastic problems in dynamics - Clarkson, Brian Leonard; Hammond, J. K.; Holmes, P. J.; Kistner, A.; Clarkson, B. L.; Kinster, A.; Clarkson, B. L. (Pitman, 1977)
Papers from the Symposium on Stochastic Problems in Dynamics, held in the University of Southampton, England, July 19 to 23, 1976, and sponsored by the International Union of Theoretical and Applied Mechanics and organised by the Institute of Sound and Vibration Research of the University.